The Impact of Gadgets on Children’s Development: Delayed Speech and Autistic Disorders - Oljabaevna, Esnazarova Zulfiya; Baxodirovna, Abdrazakova Nilufar (European Journal of Life Safety and Stability (2660-9630), 2023)
Not only do adults use devices, but also adolescents and young children as young as kindergartners and toddlers. The child’s brain is at its prime for growth between the ages of 0 and 5 years old. Because it may influence and define a child’s future development, the toddler stage is crucial for maximizing a child’s growth. The usage of technology from a young age will have an impact on children’s development and may lead to an increase in autism incidence. The goal of this study was to determine how utilizing gadgets affected autistic children’s impairments in speech and language development. The field of information and communication technology is one where technological advancements happen extremely quickly. A person’s medium for social interactions in the modern era of globalization, particularly to build social contacts and converse exclusively via gadgets. Right now, teens and young people, including children in kindergarten and toddlers, are already utilizing electronics in addition to adults. So this can lead to AUTISTIC DISORDERS.